Prevention of browning during the saccharification of juicy peach syrup and storage of peach wine / Yuxin Liu … [et al.] - Yuxin, Liu; Fangfang, He; Jiandi, Zhou; Lingkang, Chen; Guochang, Sun; Jian, Sun; Xueyuan, Han (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
Peach fruit is rich in nutrients and its fermented fruit wine is popular. However, peach fruit pulp is susceptible to browning during saccharification and wine is also prone to browning during storage, which hinders its further development. In this study, different antibrowning agents (ethylenediamine tetraacetic acid (EDTA), ascorbic acid (AA) and potassium metabisulfite (PM)) were used in the process of fruit pulp saccharification and wine storage to evaluate their antibrowning effect. Firstly, the browning inhibition ratio (BIR) was determined by single-factor experiments to select the appropriate variable concentrations. Furthermore, orthogonal experiments were designed to analyse the optimal combination of anti-browning agents. The results showed that the combination of 0.40 g/L EDTA, 0.20 g/L AA, and 0.10 g/L PM had a better anti-browning effect in fruit pulp saccharification. During the storage of peach wine, 0.15 g/L PM only had a better anti-browning effect than EDTA and AA. This study provides a reference for the anti-browning technique of peach fruit wine and further contributes to improving the quality of fruit wine.